Pendidikan Anak dengan Rahmat dan Kasih Sayang - Zubaedah, Siti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2016)
Children are one of the greatest gifts of God as a mandate (ama>nah) for parents to grow them up, make them become representative of God on earth (khali>fatullah fil ard), to spread goodness for others. Give the proper education for children is the important duty of every family. And the main foundation of education in Islam is to be in appropriate with the values ​​of religious teachings as promoted by the Prophet Muhammad Saw. As we know that to acchive succesness in our live, we have to change and become better, and the base of a change is human development who have good thought and conscience as well as faith and morals. Because of that, actually everything should ideally always be associated with the rahmat (mercy) and love as human fitrah, that he is a creature that has a sense of love. It also should be manifested in educating children. This article discusses and offers the solution for parent to educate their children with mercy and love, and also in order to make it suitable with the needs of them for their future, both for themselves and also others.